The relationship between technical innovation and financial performance in shipping firms - Kouspos, Andreas; Panayides, Photis; Tsouknidis, Dimitris (My University, 2023)
This study investigates the relationship between financial performance and technical innovation of 21 listed shipping firms employing a panel data methodology. Using vessel-level and firm-level data over the period 2013 to 2019, we show that vessels’ technical innovation exhibits a positive relationship with firms’ financial performance. We identify three types of technical innovation for listed shipping firms, namely ice-class, eco, and propulsion types, and show that shipping firms operating eco-type ships exhibit higher financial performance on average during the sample period examined. This result has important implications not least on the decision-making of shipping firms to invest in technically innovative ships.
Keywords: Eco-type ships; Financial performance; Listed shipping frms; Technical innovation; Ice class ships